(untitled) (Web of Teachers: Inderscience Research, 2025)
This article discusses the ethics and features of translation in English and Uzbek, as well as the relationship between people who speak different languages, and the etiquette of translators in the translation process. This article is written about the features of the English and Uzbek languages in translation, and discusses their linguistic, linguocultural and specific features. Since both languages belong to different language families and are very distant in terms of territory, many different aspects have been identified that differ from each other. As a guide for translators, the existence of relevant rules and ethics contained in the translators’ code of conduct is scientifically discussed, and the problems and solutions in translation ethics are discussed.